Mobile Motion Advisor - a feedback system for physical exercise in schools - Preuschl, E.; Baca, A.; Novatchkov, H.; Kornfeind, B.; Bichler, S.; Böcskör, M. (Procedia Engineering, 2010)
The Mobile Motion Advisor (MMA) is a mobile feedback system designed to support high school students by giving them instructions during their physical exercises based on the integration of up-to-date sensor, data transmission and processing technologies to provide optimal training assistance. The aim is to give individually customized exercise instructions. We expect students to develop a positive attitude towards physical exercising when they do not experience frustration due to overstrain. This article gives an overview of the system architecture of the MMA framework and highlights some of the implementations.